The Use of A Digital Multimodal Textbook to Foster Students’ English Proficiency - Sitti Aisyah; Nuraeni Nuraeni (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
This research aimed to determine students’ English language proficiency after conducting an experiment. A method that was implemented was the use of a digital multimodal textbook application called Book Creator. This method focused on teaching students the English language using a digital textbook that promoted multimodality. In the test book, some modes were applied (teacher’s voice recorded, videos from the internet, and pictures). This research was a pre-experimental method that used one group sample. The research data was collected to measure the effectiveness of the method using pre-and post-test as the research instrument. From the data, it was found that the use of a digital multimodal textbook gave improvement to most of the student's English language proficiency. However, a few students only experienced a little improvement. The data shows that there was a significant difference in students’ scores between the pre-and post-test. The mean score in the pre-test was 47.81with the minimum score being 26 before the treatment. Meanwhile, after the application of the digital multimodal textbook, the mean score of the post-test encountered improvement to 65.50 and the minimum score was 40. From the data, it was revealed that even though most of the students gained a better understanding after the treatment. However, a few students still had difficulty upgrading their English language proficiency.